(untitled) (Anuario Filosófico, 2018)
This paper examines the analysis of judgements of belief that Wittgenstein offers in 5.54–5.5423 of the Tractatus. We offer an interpretation of these paragraphs wich also pays attention to 5.5423, usually forgotten. In our opinion, this interpretation fits with Wittgenstein’s doctrines, and makes clear that such non-genuine propositions are nonsense. These are not, as has sometimes been proposed, the propositions of psychology. In the second part of the article we give a detailed discussion of interpretations of these paragraphs which have been offered previously.